Liberal hemoglobin threshold affects cerebral arterial pulsed Doppler and cardiac output, not cerebral tissue oxygenation: a prospective cohort study in anemic preterm infants. Issue 10 (16th July 2019) - Jani, Pranav; Lowe, Krista; Hinder, Murray; Galea, Claire; D'Çruz, Daphne; Badawi, Nadia; Tracy, Mark
Abstract : BACKGROUND: Red blood cell (RBC) transfusion is a standard treatment for anemia of prematurity. Cerebral tissue oxygenation and blood flow velocities improve when a restrictive transfusion threshold is followed, but little is known about the effect of practicing a liberal transfusion threshold on cerebral tissue oxygenation, cerebral blood flow velocities, and cardiac output measurements. STUDY DESIGN AND METHODS: A prospective observational study of preterm infants under 32 weeks' gestation who received RBC transfusion. Monitoring was performed immediately before, immediately after, and 24 hours after transfusion. Data obtained included physiologic parameters, cerebral tissue oxygenation index (TOI), anterior and middle cerebral artery pulsed Doppler ultrasound measurements, and cardiac output measurements. Data were analyzed using analysis of variance for repeated measures. RESULTS: Fifty RBC transfusion episodes in 40 preterm infants were monitored. The mean gestational age was 26.72 weeks (±1.6 weeks), and the mean birth weight was 855.25 g (±190.7 g). We did not observe significant changes in cerebral TOI (pretransfusion mean TOI = 70.5 [11.54], immediately after transfusion = 71.38 [12.51], [p = 0.924; 95% confidence interval (CI), −4.64 to 6.39], and 24 hours after transfusion = 75.64 [14.4]; [p = 0.07; 95% CI, −0.37 to 10.65]), cerebral fractional tissue oxygen extraction (pretransfusion = 0.25 [0.12], immediately after transfusion = 0.24 [0.13], and 24 hours after transfusion = 0.20 [0.15]), cerebral resistive index, cerebral pulsatility index, or right ventricular output. Statistically significant changes were observed immediately after transfusion in peak systolic velocity, end‐diastolic velocity and time‐averaged maximum velocity in the cerebral arterial circulation. Left ventricular output (pretransfusion = 374.32 mL/kg/min, immediately after transfusion = 346.67 mL/kg/min [p = 0.000; 95% CI, –39.61 to −15.68], and 24 hours after transfusion = 361.17 mL/kg/min [p = 0.027; 95% CI, –25.11 to −1.18]) and heart rate (pretransfusion = 163.37 [9.49], immediately after transfusion = 157.29 [10.2] [p = 0.000; 95% CI, –8.96 to −3.20], and 24 hours after transfusion = 160.40 [10.4] [p = 0.041; 95% CI, –5.85 to −0.09]) showed statistically significant changes throughout the monitoring period. CONCLUSION: Our findings show that practicing liberal transfusion thresholds did not improve cerebral TOI in preterm infants who have mild anemia, but it did improve the compensatory response in cerebral arterial blood flow and cardiac output.